A Study of energy loss in LiFePO4 battery-balancing schemes for electric vehicle applications - Amtip, Adisorn; Phatrapornnant, Teera; Nuthong, Chaiwat; Kaewpunya, Amaras (My University, 2014)
High energy density LiFePO4 battery plays an important role in the EV application. Due to strictly charging requirement, battery balancing is a necessary function in a battery management system (BMS) for charging this type of battery. Normally, there are two types of battery balancing circuit, i.e. active and passive balancing circuit. Because of simplicity, a passive circuit is chosen. Technically, passive balancing has energy loss while batteries are balancing. This research is focused on exploring three kinds of passive-balancing schemes about energy loss and at various conditions e.g. considering at balancing current or state of charge among all cells (SOCmax - SOCmin). The simulation results show that the different balancing schemes do not have significant effect on energy loss.
Keywords: energy loss; EV application; LiFePO4; passive balancing; State Of Charge(SOC)